IMPLEMENTATION OF THE ARM'S LENGTH PRINCIPLE IN RELATED PARTY RELATIONSHIPS AT PT S INDONESIA - Rafida Nuraini; Hanung Triatmoko; Oscar Prasetyo Adhi; Asaprima Putra Karunia (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
This study aims to analyze the implementation of Arm’s Length Principle by PT S Indonesia in affiliated transactions with SF Co., Ltd, a parent company from Japan. The focus of the study is to assess the suitability of determining fair prices with tax regulations in Indonesia. The research method used is descriptive qualitative through interviews with tax consultants who handle the company’s transfer pricing. The analysis is carried out based on Transfer Pricing documentation and applicable tax provisions. The results of the study indicate that the use of the Transaction Net Margin Method (TNMM) is in accordance with the business characteristics of PT S Indonesia. Testing using the Profit Level Indicator (PLI) with the Berry Ratio method shows that the company’s position is within the fair range, especially in the lower interquartile. In conclusion, PT S Indonesia has implemented tax obligations in accordance with the fairness principle without any indication of tax avoidance practices, although there are obstacles in finding comparable comparisons.